Macroeconomic impacts of climate-induced damages in Ireland: A CGE analysis of secondary impacts - Kelly C. De Bruin; Clement Kweku Kyei; Loïc Henry; Aykut Mert Yakut (The Economic and Social Research Institute (ESRI), 2024)
Designing and implementing effective and efficient climate policies requires an understanding of climate change impacts. However, the estimation of climate change impacts remains lacking, without an understanding of the sectoral details of climate change impacts and their further impacts on the wider economy. In this paper, we apply a production function approach to implement several climate change impacts into an intertemporal computable general equilibrium (CGE) model of the Irish Economy, the I3E model. Our results show that, without adaptation, coastal impacts on the macroeconomy will be the highest, followed by labour productivity impacts. Examining different household types, we find that richer households are impacted more than poorer. In this paper we account for interlinkages between sectors, and show how climate change impacts impact other parts of the economy, which is neither clearly assessed in econometric assessments within the literature, nor in classic Integrated Assessment Models with few consisting of production sectors.
Keywords: 330; Climate change; macroeconomy; impact assessment; CGE modelling; Ireland